2021
DOI: 10.1002/anie.202105921
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (−)‐Spiroxins A, C, and D

Abstract: Spiroxins A, C, and D are metabolites that have been identified in the marine fungal strain LL‐37H248. Their unique polycyclic structures and intriguing biological activities make them attractive targets for the synthetic community. Based on a scalable enantioselective epoxidation of 5‐substituted naphthoquinone, an oxidation/spiroketalization cascade, ortho‐selective chlorination of the phenol unit, and oxime‐ester‐directed acetoxylation, an enantioselective total synthesis of (−)‐spiroxins A and C and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…271 A homodimeric bispyrrolidinoindoline dioxopiperazine alkaloid isolated from sponge-derived Aspergillus violaceofuscus has been prepared, 272 and synthesis of chlorinated alkaloids gymnastatin G and dankastatins B and C has also been achieved. 273 Cyclohexenone derivative pleosporol A (and its stereoisomers) has been prepared from arabinose, 274 peniciaculins A and B and hydroxysydonic acid have been synthesised via an enantioselective method, 275 as have (+)-peniciketals A and B, 276,277 and (−)-spiroxin D. 278 In silico prediction of SARS-CoV-2 main protease binding ability for marine fungal compounds predicted wailupemycins H and I, and cottoquinazoline B to have high nanomolar inhibition for preventing viral replication, 279 and another in silico study indicated that epolactaene would also inhibit this protease. 280 3-Bromoascochlorin suppressed small cell lung cancer growth in a xenogra mouse model without affecting body weight.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…271 A homodimeric bispyrrolidinoindoline dioxopiperazine alkaloid isolated from sponge-derived Aspergillus violaceofuscus has been prepared, 272 and synthesis of chlorinated alkaloids gymnastatin G and dankastatins B and C has also been achieved. 273 Cyclohexenone derivative pleosporol A (and its stereoisomers) has been prepared from arabinose, 274 peniciaculins A and B and hydroxysydonic acid have been synthesised via an enantioselective method, 275 as have (+)-peniciketals A and B, 276,277 and (−)-spiroxin D. 278 In silico prediction of SARS-CoV-2 main protease binding ability for marine fungal compounds predicted wailupemycins H and I, and cottoquinazoline B to have high nanomolar inhibition for preventing viral replication, 279 and another in silico study indicated that epolactaene would also inhibit this protease. 280 3-Bromoascochlorin suppressed small cell lung cancer growth in a xenogra mouse model without affecting body weight.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…In 2021, attracted by the promising biological activities and challenging polycyclic architecture, Hu and coworkers designed another route to synthesize (−)‐spiroxin C, followed by the late‐stage functional group transformation to afford (−)‐spiroxin A and D (Scheme 11). Notably, the commercially available juglone 11 ‐ 1 was the only starting material [52] . At the beginning, 11 ‐ 3 was prepared as a single product through the sequence hydroxy group protection by 4‐methylbenzyl, enantioselective epoxidation catalysed by cinchona, then regioselective and diastereoselective reduction using (CH 3 ) 4 NBH(OAc) 3 , and hydroxy group protection with TBS group.…”
Section: Total Synthesis and Structure Revision Of Spirobisnaphthalenesmentioning
confidence: 99%
“…Notably, the commercially available juglone 11-1 was the only starting material. [52] At the beginning, 11-3 was prepared as a single product through the sequence hydroxy group protection by 4-methylbenzyl, enantioselective epoxidation catalysed by cinchona, then regioselective and diastereoselective reduction using (CH 3 ) 4 NBH(OAc) 3 , and hydroxy group protection with TBS group. Moreover, the epoxide unit of 11-3 was identical to those of natural products identified with the X-ray crystallographic analysis.…”
Section: Total Synthesis Of Type C Spirobisnaphthalenesmentioning
confidence: 99%
“…These simple and effective approaches overcome the inherent disadvantages of RTP crystalline materials, such as harsh growth environments, challenging preparation processes, and inferior reproducibility. [ 27 ] Although polymeric RTP materials are superior to crystalline materials in terms of preparation, flexibility, and transparency, there are still certain limitations. The short lifetimes in polymeric RTP systems are primarily caused by the extremely rapid and severe nonradiative decay of triplet excitons.…”
Section: Introductionmentioning
confidence: 99%